Biosynthesis of Fe/Pd Bimetallic Nanoparticles and Used for Removal of Synthetic Oily Wastewater - Hassan, Ahmed Khudhair; Hashim, Luay Q.; Rezooqi, Ahmed M.; Hashim , Mohammed F. (Journal of Petroleum Research and Studies, 2024)
Eucalyptus plant leaves aqueous extract was used to produce a green bimetallic Fe/Pd nanoparticles (G-Fe/Pd NPs) catalyst for the degradation of synthetic oily effluent. Using Brunauer-Emmett-Teller (BET) analysis, Fourier-transform infrared spectroscopy (FTIR), particle size, and a zeta potential analyzer, the synthesized G Fe/Pd NPs were evaluated. G-Fe/Pd NPs have been found to contain nanoparticles, with a mean size of 182 nm and a surface area of 5.106 m2/g. The resulting nanoparticles were then used as a catalyst for a Fenton-like reaction. The amount of green catalyst G-Fe/Pd NPs (0.125-0.5 g/L), H2O2 concentration (15-37.5 mmol/L), pH (3-7), and temperature (25-45°C) all have a significant impact on the degradation efficiency of synthetic oily wastewater. Batch experiments showed that 88.9% degraded chemical oxygen demand (COD) from synthetic oily wastewater within the optimum conditions of peroxide concentration, catalyst dose, pH, and temperature which were 30.0 mmol/L, 0.375 g/L, 3, and 45℃ respectively along with 60 min contact time. The results of kinetic models showed that oily wastewater removal followed the Behnajady-Modirshahla-Ghanbary (BMG) model. Finally, the thermodynamic study of the reaction was also examined and concluded to endothermic reaction with an enthalpy of 37.39 kJ/mol.